FORECASTING THE BASIC CONDITIONS OF INDONESIA'S RICE ECONOMY 2019-2045 - Arifin Zainul; Nuhfil Hanani; Djoko Kustiono; S Syafrial; Rosihan Asmara (Agricultural Socio-Economics Journal, 2021)
By 2045, Indonesia's population is expected to reach 321.4 million, the fifth largest in the world after China, India, Nigeria, and the United States. It is an excellent challenge for Indonesia to provide food in the future as it keeps pace with the rapid population growth. This study aims to analyze forecasting the basic conditions of Indonesia’s rice economy 2019-2045. The research data use time-series data from 1961-2018, including data from the Central Bureau of Statistics (BPS), Ministry of Agriculture/Pusdatin, Food and Agriculture Organization (FAO), International Rice Research (IRR), Department of Commerce, United States Department of Agriculture (USDA), and ASEAN Food Safety Information System (AFSIS). Data analysis using the simultaneous equations model approach. The results show that in 2019-2045 the projection of rice productivity in 2025 is 64,465 quintals per hectare; in 2035, it is 68,797 quintals per hectare, and in 2045 it is 77,462 quintals per hectare. In 2045, the projected land area is 27.64 million hectares. Although Indonesia is forecast to experience a rice surplus of 37.80 million tonnes in 2045, the projected rice production and domestic rice consumption level indicate the potential for rice imports of 15 million tonnes.